Konstrukcja odpowiedzialności podmiotów zbiorowych za czyny zabronione pod groźbą kary, w aspekcie fundamentalnej zasady porządku prawnego — prawa do obrony - Majowska, Aneta Teresa (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
The article focuses on the fundamental right of asubject exposed to negative consequences during criminal proceedings. The determination of the scope of a constitutionally and statutorily granted right of defence, in particular in the light of the access to the dossier by the collective body’s counsel and by the collective body itself, as well as the analysis of the construction of collective body’s responsibility, point to the legal restrictions regarding the right of defence on grounds of the act on responsibility of collective bodies for acts prohibited under penalty. It has been emphasized that acollective body holds no right of access to the evidence gathered during proceedings against anatural person, the result of which may directly impose the criminal responsibility of the collective body, effecting in certain negative consequences, including imposition of a penalty. The specific nature of collective bodies’ responsibility has drawn demands towards the capacity of a collective body to influence the proceedings in progress.
Keywords: podmioty zbiorowe; odpowiedzialność karna; prawo do obrony; postępowanie karne; dostęp do akt sprawy